PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS BORLAND DELPHI 7 PADA MATERI GELOMBANG ELEKTROMAGNETIK - Neiny Edwana; M. Rahmad '; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Physical learning especially the material of electromagnetic waves is an abstract material and difficult to observe. The main purpose of this research is to develop a valid Borland Delphi 7 based learning media on electromagnetic wave material. This research was conducted in December 2016 until June 2017 at the Physics Education Laboratory of Universitas Riau. The design of learning media development follows the stage of ADDIE (Analyze, Design, Development, Implementation, Evaluation). Validation of this instructional media program includes content of material and design of media itself. Based on the results of data analysis, it is found that the learning media developed in this study has a very high validity value of both assessed aspects. For validity of learning media subject matter this result of validation by expert is 3.61 and validation by teacher is 3.6 so it is relevant with physics concepts that will be taught by using this media, while for validity of media design by expert is 3.5 and by teacher 3.62 so media This study's learning can be declared eligible to be used to support schooling.Key words: Electromagnetic Wave, Media Based On Borland Delphi 7, ADDIE